3D-PTV flow measurements of Newtonian and non-Newtonian fluid blending in a batch reactor in the transitional regime. (31st December 2021) - Romano, M.G.; Alberini, F.; Liu, L.; Simmons, M.J.H.; Stitt, E.H.
Highlights: 3D-PTV was used to study transitional flows in a lab-scale stirred vessel. Newtonian and non-Newtonian rheology influence the impeller pumping capacity. Metzner-Otto's model in the transitional regime was assessed and refined. In the impeller region, shear rate and acceleration were highly correlated. Abstract: Lagrangian trajectories obtained through 3D Particle Tracking Velocimetry (3D-PTV) measurements have been used to visualize the flow field of Newtonian and non-Newtonian fluids in a flat-bottomed vessel. The vessel, of diameter T = 180 mm, was equipped with a 6-blade Rushton turbine of diameter D = T / 3 and four baffles of width b = T / 10 . The experiments were carried out in the transitional flow regime ( 73 ≤ R e ≤ 1, 257 ). The velocities and Lagrangian accelerations in the flows have been calculated from the time-resolved tracer coordinates. Non-Newtonian fluids exhibited a smaller impeller flow number compared to Newtonian fluids. The distributions of shear rate have been obtained via interpolation of the Lagrangian velocity data in a 3D Eulerian grid. In the impeller region, the mean shear rate was, to a first approximation, proportional to the impeller rotational speed, although a more detailed analysis revealed influences of both rheology and Reynolds number. The mean Lagrangian acceleration scaled with the mean shear rate raised to the power of 1.8 .